Numerical Investigation of Hurricane-Induced Failure of a Military Tent - KOSIUCZENKO, Krzysztof (Engineering Transactions, 2023)
The subject of this research was the analysis of a numerical case of catastrophic destruction of a large-area military tent under the influence of a hurricane impact. As a result of the research, the level of the destructive load was identified, and the construction failure process was reconstructed. The practical effect of the work was the conclusion on the reinforcement of the structure. The calculations were made using the finite element method in the LS Dyna calculation program.